HUBUNGAN POSTUR KERJA DENGAN METODE QUICK EXPOSURE CHECKLIST (QEC) PADA KELUHAN NYERI LEHER - Muchamad Satria Pujasakti; Baju Widjasena; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Neck pain complaints are complaintspain located in the posterior region of the Cervical Spine (C1-C8), of the Superior Nuchal Line until T1 with or without spreading to the head, trunk, and upper extremities.Working posture while sewing in the work area could become a risk factor for neck pain on a sewing operator. The purpose of this study was to analyze the correlation between work posture with neck pain complaints on standing sewing operators. Cross-sectional study which is a form of observational studies and descriptive analytic was used in this research. Samples of the study were 91 people standing sewing operators chosen with a purposive sampling method. Visual Analog Scale (VAS) was used in the neck pain complaints questionnaires for a subjective measurement and work posture is measured using Quick Exposure Checklist (QEC). Spearman rank correlation test was used for statistical analysis. The results showed no relationship between work posture and neck pain (p = 0.031). Business owners should provide training and additional insight on ergonomic working postures for workers, and conduct a physical examination for an early neck pain detection and to preserve workers health. Companies shouldalso improve the work station with an adjustable table that can be easily raised and lowered.